2018
DOI: 10.1136/jech-2018-210568
|View full text |Cite
|
Sign up to set email alerts
|

Are happy people healthier? An instrumental variable approach using data from Greece

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…However, the ndings from this study indicated that inequality in happiness is real and is highly depends on some socioeconomic factors that are also responsible for other sorts of inequalities. As such recently Kyriopoulos et al provided evidence that a strong relationship exist between happiness and self-reported health among lower educated and those from lower socioeconomic status [14].…”
Section: Discussionmentioning
confidence: 96%
“…However, the ndings from this study indicated that inequality in happiness is real and is highly depends on some socioeconomic factors that are also responsible for other sorts of inequalities. As such recently Kyriopoulos et al provided evidence that a strong relationship exist between happiness and self-reported health among lower educated and those from lower socioeconomic status [14].…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have shown positive effects of subjective well-being on physiological health. For instance, literature has revealed that happy individuals have better self-rated physical health [ 35 ]. In addition, subjective well-being is also linked with a reduced likelihood of all-cause morbidity among the older population [ 36 ].…”
Section: Subjective Well-beingmentioning
confidence: 99%
“… The case of using a binary endogenous variable with 2SLS was analysed by Angrist and Psichke (2008), who reached the conclusion that using the “garden‐variety 2SLS” (i.e. common 2SLS, in which having a binary treatment means having a linear probability model in the first stage) would be the best alternative (Kyriopoulos et al, 2018; Carlin, Olafsson, & Pagel, 2019). Thus, this is the methodology that we employed in the present study.…”
mentioning
confidence: 99%